A Polar 18F‐Labeled Amino Acid Derivative for Click Labeling of Biomolecules. Issue 17 (28th April 2014) - Schieferstein, Hanno; Ross, Tobias L.
Abstract: This work describes the synthesis and 18 F‐labeling of an amino acid based prosthetic group that is able to participate in copper(I)‐catalyzed cycloadditions. The prosthetic group can be used for 18 F labeling of biomolecules under mild conditions. The synthesis started withL ‐serine methyl ester, which was derivatized by introducing an alkyne moiety and a leaving group for 18 F labeling. Subsequently, 18 F labeling as well as deprotection conditions were screened, which resulted in an overall radiochemical yield (RCY) of around 28 %. Furthermore, the 18 F‐labeled prosthetic group was treated with an azido cyclic Arg‐Gly‐Asp (cRGD) peptide as a model system in very high RCY of 98 %. Abstract : Click it like alanine: The endogenous amino acid serine is derivatized to be able to participate in copper(I)‐catalyzed cycloadditions and to carry a 18 F label. The organic synthesis and the 18 F labeling are screened and optimized. The 18 F‐labeled prosthetic group is "clicked" to an azido‐functionalized cyclic Arg‐Gly‐Asp (RGD) as proof of principle.